Control Dilution and Distribution of Ownership - Morten Bennedsen; Mogens Fosgerau; Daniel Wolfenzon (Copenhagen Business School (CBS), Department of Economics, 2000)
We investigate the patterns of ultimate distribution of ownership in a sample of small closely held corporations. Motivated by recent corporate governance theories we define control dilution as the absenc of a single dominating shareholder. Most firms have one or two ultimate owners implying that control is very concentrated. However, we find strong evidence for control dilution in firms with multiple owners and we proceed to analyze three potential explanations: a general strategic motive, a coalition formation argument and the presence of family ownership. We find the strongest evidence for a general strategic motive and we clearly reject that the observed control dilution is due to family ownership. Finally, we show that the probability of control dilution increases with manager ownership and number of owners, but decreases with the age of the firm and with the presence of family ownership.
hdl:10398/7614
Keywords: G32; G34; 330; Ownership Distribution; Control Allocation; Closely Held Corporations